A Meta Analysis of Factors Affecting Teaching and Student Learning in Higher Education - Chaudhary, Priya; Singh, Reetesh K. (Frontiers in Education, 2022)
The objective of this study was to conduct a meta analysis of studies conducted in the past on effective teaching and its impact on student learning outcomes. Meta analysis is a powerful tool for synthesizing previous research and empirically validating theoretical frameworks. For this purpose, the dynamic model of educational effectiveness was used as a guiding framework to select and organize 132 studies examining the impact of teaching factors on student learning outcomes. The teaching factors of dynamic model were found to be moderately associated with learning outcomes. Various moderators like level of education and type of study were also identified. The study has various theoretical, methodological and practical implications. The study points out that when it comes to teaching, imposing non-essential and superfluous dichotomies between different teaching approaches might be impractical. The findings of this meta analysis may also provide implications for practitioners and policymakers especially in the domain of faculty development and education programs. It can give existing or prospective teachers an opportunity to practice and rehearse these factors in classroom, reflect on them and receive feedback on how their practice can be improved.